Development of a mitochondria-targeted fluorescent probe for hydrazine monitoring in living cells. Issue 112 (23rd November 2016) - Ran, Yu-Zhao; Xu, Hao-Ran; Li, Kun; Yu, Kang-Kang; Yang, Jin; Yu, Xiao-Qi
Abstract : A novel mitochondria-targeted fluorescent probe was presented, which could image exogenous hydrazine in living cells. Abstract : A coumarin-based fluorescent probe (mito-N2 H4 ) for hydrazine was presented, which could detect hydrazine with high sensitivity and excellent selectivity. Importantly, mito-N2 H4 is the first mitochondria-targeted fluorescent probe to image exogenous hydrazine in living cells.